2006
DOI: 10.1007/s11104-005-3502-y
|View full text |Cite
|
Sign up to set email alerts
|

Congeneric Serpentine and Nonserpentine Shrubs Differ More in Leaf Ca:Mg than in Tolerance of Low N, Low P, or Heavy Metals

Abstract: Serpentine soils limit plant growth by NPK deficiencies, low Ca availability, excess Mg, and high heavy metal levels. In this study, three congeneric serpentine and nonserpentine evergreen shrub species pairs were grown in metalliferous serpentine soil with or without NPKCa fertilizer to test which soil factors most limit biomass production and mineral nutrition responses. Fertilization increased biomass production and allocation to leaves while decreasing allocation to roots in both serpentine and nonserpenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…Numerous studies have shown differences in Mg and Ca uptake by serpentine and non-serpentine populations of the same plant species when grown in a serpentine substrate (e.g., Johnston and Proctor 1981;O"Dell et al 2006;Sambatti and Rice 2007). Higher Ca and lower Mg uptake, resulting in significantly higher shoot Ca/Mg ratios, have frequently been recorded for serpentine plants, suggesting that selective Ca accumulation and Mg exclusion and/or sequestration by roots are important evolutionary adaptations of serpentine species (O"Dell et al 2006;Kazakou et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown differences in Mg and Ca uptake by serpentine and non-serpentine populations of the same plant species when grown in a serpentine substrate (e.g., Johnston and Proctor 1981;O"Dell et al 2006;Sambatti and Rice 2007). Higher Ca and lower Mg uptake, resulting in significantly higher shoot Ca/Mg ratios, have frequently been recorded for serpentine plants, suggesting that selective Ca accumulation and Mg exclusion and/or sequestration by roots are important evolutionary adaptations of serpentine species (O"Dell et al 2006;Kazakou et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Higher Ca and lower Mg uptake, resulting in significantly higher shoot Ca/Mg ratios, have frequently been recorded for serpentine plants, suggesting that selective Ca accumulation and Mg exclusion and/or sequestration by roots are important evolutionary adaptations of serpentine species (O"Dell et al 2006;Kazakou et al 2008). In the present experiment, a direct comparison of Ca and Mg uptake in serpentine and non-serpentine populations of K. arvensis was not possible due to their cultivation in native substrates that differed in available Ca and Mg concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Communities with a high level of soil Cu (I, II, III) also differed in other parameters including nutrients. Metallicolous communities associated with higher nutrient concentrations than other communities, differ from those on serpentine soils, where deficiency of N, P, K and Ca has been suggested as a potential reason for limited plant productivity (Kruckeberg 1984, O'Dell et al 2006. Communities with a lower Cu contamination (IV, V) also differed from each other notably in Fe and Mg.…”
Section: A C D Bmentioning
confidence: 99%
“…Similar patterns are observed in eastern parts of the Katangan Copperbelt (unpublished data). This, however, differs from serpentine soils where deficiency in NPK and Ca has been suggested as a potential reason for the limited plant productivity (Kruckeberg 1984;O'Dell et al 2006;Proctor 1971;Whittaker 1954). While poorer in number of species per 1 m 2 , Steppes host a larger number of endemics with higher occurrences per 1 m 2 .…”
Section: Diversity Of Plant Communitiesmentioning
confidence: 94%